Implikasi Ekonomi dari Penurunan Produksi Minyak Mentah terhadap Kebutuhan Impor dan Defisit Energi (Analisis tren produksi dan ekspor-impor BBM) - Dirmansyah Darwin; I Made Jyotisa Adi Dwipatna; Muh. Fardan Ngoyo; Abdul Rahman; Hafid Sumarwadji (Indonesian Journal Publisher, 2025)
This study analyzes the implications of the production decline of crude oil in Indonesia on import dependency and the national energy deficit during 2018–2023. Using a descriptive quantitative approach and trend analysis of secondary data, the research shows that the decline in oil production is due to the dominance of aging oil wells, limited new exploration, and structural challenges in the upstream oil and gas sector. Meanwhile, energy consumption, particularly fuel, has increased sharply, driven by the transportation and industrial sectors. This gap has resulted in surge in the volume and value of crude oil and refined product imports, weakening national energy security. Calculations of the import dependency ratio indicate that more than 40% of fuel consumption is met through imports. This has resulted in a higher foreign exchange burden, pressure on the rupiah exchange rate, and a widening current account deficit. This research suggests considering increasing national oil lifting through Enhanced Oil Recovery (EOR), diversifying energy sources by strengthening the development of New and Renewable Energy (NRE), and reforming energy subsidies to ensure better targeting. In addition, reformulation of energy policy to reduce economic vulnerability and strengthen national energy security would be key step to respond the situation.